The German Spy in America : The Secret Plotting of German Spies in the United States and the Inside Story of the Sinking of the Lusitania - Jones, John Price, 1877-1964; Roosevelt, Theodore, 1858-1919; Wood, Roger B. (Salt Lake City, UT : Project Gutenberg, 2017)
"The German Spy in America" by John Price Jones is a historical account written in the early 20th century. The work delves into the clandestine activities and schemes perpetrated by German spies operating within the United States during World War I, shedding light on the plots and machinations that sought to compromise American sovereignty in favor of the Nazi agenda. The book is rich in detail, utilizing official government records and investigative journalism to document these covert operations. At the start of the narrative, the author sets the stage by introducing the pervasive presence of German espionage on American soil, particularly focusing on New York City as the hub of their operations. Noteworthy figures like Captain Franz von Papen are identified as key players orchestrating various plots that aimed to undermine the war effort of the Allies, including attempts at sabotage and insurrection. The opening portion outlines how these agents sought to manipulate public sentiment and exploit America$1 (Bs neutrality, driving home the urgency of addressing the threats posed by these internal conspirators. Overall, it paints a compelling picture of a silent but dangerous conflict occurring just beneath the surface of society during a tumultuous period. (This is an automatically generated summary.)s
The American edition published under title: America entangled.
Release date is 2017-10-02
E-text prepared by Richard Tonsing and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Germans -- United States; World War, 1914-1918 -- Secret service -- Germany; Espionage, German -- United States -- History -- 20th century; World War, 1914-1918 -- Secret service -- United States; Spies -- Germany -- Biography; Spies -- United States -- Biography